2015
DOI: 10.14740/jocmr2250w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Energy Expenditure and Oxygen Consumption of Spontaneous Breathing Trial Conducted With and Without Automatic Tube Compensation

Abstract: BackgroundWeaning from mechanical ventilation is defined as the process of release of ventilatory support and how the evaluation of this phase is conducted in the spontaneous breathing trial (SBT). One of the most used modes of SBT is the continuous positive airway pressure (CPAP), which applies a continuous positive pressure in both inspiration and expiration. However, together with the mechanical ventilation modes, the automatic tube compensation (ATC) can be used, which compensates the resistance imposed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…However, a recent meta-analysis revealed no significant difference in successful extubation rate between the T-piece and PS groups [19]. In recent years, ATC has been developed to assess the possibility of discontinuing mechanical ventilation [8], which was considered to have a similar mechanism with PSV [33]. However, different from PSV, the preset pressure of ATC model can be modified according to the conditions [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent meta-analysis revealed no significant difference in successful extubation rate between the T-piece and PS groups [19]. In recent years, ATC has been developed to assess the possibility of discontinuing mechanical ventilation [8], which was considered to have a similar mechanism with PSV [33]. However, different from PSV, the preset pressure of ATC model can be modified according to the conditions [34].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the ATC is to compensate the airway resistance caused by the trachea catheter, and eventually reduce the extra work of patients' autonomous respiration [8]. Some studies [9][10][11] suggested that ATC should be preferably prescribed to guide ventilator weaning in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…At present, T-piece, continuous positive airway pressure (CPAP), pressure support ventilation (PSV), and automatic tube compensation (ATC) are the most common ventilation techniques (11,12,(15)(16)(17)(18)(19)(20). SBT strategies focused in this study can be categorized into three categories as follows: (a) providing constant or dynamic ventilatory support to counteract the resistance of the endotracheal tube such as PSV and ATC (21)(22)(23), (b) providing continuous positive pressure in both inspiration and expiration to enhance breathing mechanics and reduce the effort needed by mechanically ventilated patients with airflow obstruction such as CPAP (24)(25)(26)(27), and (c) accelerating spontaneous breath of patients without positive pressure support such as T-piece, which is related to more frequent respiratory activity and consumption of more oxygen (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…No presente estudo, a média destes valores foi entre 0,68 a 0,82, conferindo a confiabilidade das medidas. Para a obtenção de valores precisos, além do conhecimento técnico e da experiência prévia dos autores com calorimetria (AUXILIADORA-MARTINS et al, 2011;LAGO et al, 2015;PICOLO et al, 2016), alguns critérios recomendados foram seguidos, como a checagem de vazamentos dos gases respirados, a calibração, a exclusão de pacientes com drenos e fístulas, com frações inspiradas de oxigênio maior que 60% e da PEEP maior que 20 cmH2O. Apesar desta variável ter apresentado uma diferença estatística significativa, quando comparado os valores ente o repouso e a intervenção, nos pacientes em choque séptico (< 72 horas), este valor não tem significância clínica.…”
Section: Dados Metabólicos Sepse E Choque Séptico (>72h) N=21unclassified